Obituaries and predictions: a sociological perspective on the future of religion - J. Beyers (Acta Theologica)
Religion is a social phenomenon. Society and, therefore, religion will continue to exist as long as human beings exist. This article explores this syllogism, by analysing two 19th-century social theories on the future of religion. Weber was not positive as to the future of religion and foresaw that religion would die out at the hands of rationality and modernisation. Durkheim predicted that religion would suffer at the hands of rationality and modernisation, but that it would not die out completely. It would disappear from the public domain and become a private matter. As private matter, religion might even grow, according to Durkheim. These theories became the framework for all theories on religion and secularisation. Berger, Luckmann and others followed along these lines. A new appraisal of where we currently stand with the effects of secularisation on religion is necessary. At present, religion is perceived as being vibrant and active. There are reasons why religion did not disappear or become invisible as was predicted. The article investigates certain key characteristics of current society in order to determine the nature of religion in the future. It examines the role of pluralism, individualism and the effect of uncertainty. The result as to the future of religion is a dichotomy of continuity and discontinuity.